2013
DOI: 10.1016/j.jaci.2012.10.029
|View full text |Cite
|
Sign up to set email alerts
|

TACI mutations and impaired B-cell function in subjects with CVID and healthy heterozygotes

Abstract: Background Mutations in the gene coding for the transmembrane activator and calcium-modulating cyclophilin ligand interactor (TACI) are found in 8% to 10% of subjects with common variable immunodeficiency (CVID). Although heterozygous mutations may coincide with immunodeficiency in a few families, most mutation-bearing relatives are not hypogammaglobulinemic. Thus, the role of TACI mutations in producing the immune defect remains unclear. Objective This study examined the expression and function of TACI muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 36 publications
1
65
0
1
Order By: Relevance
“…Previously, the association between TACI mutation(s) and CVID was unclear because many people carrying TACI mutations are healthy and without infectious susceptibility or decreased serum immunoglobulins (18,41). However, we found that all individuals with TACI mutations failed to remove developing autoreactive B cells in the marrow.…”
Section: Discussionmentioning
confidence: 70%
“…Previously, the association between TACI mutation(s) and CVID was unclear because many people carrying TACI mutations are healthy and without infectious susceptibility or decreased serum immunoglobulins (18,41). However, we found that all individuals with TACI mutations failed to remove developing autoreactive B cells in the marrow.…”
Section: Discussionmentioning
confidence: 70%
“…6 To assess the ability of the TACI to bind BAFF and APRIL in the presence of Fc block, cells were incubated with 100 ng/mL of FLAG-tagged BAFF or FLAG-tagged APRIL (Axxora, San Diego, CA). The cells were washed and examined with streptavidinphycoerythrin by FACS.…”
Section: Surface Expression Of Taci and Ligand Bindingmentioning
confidence: 99%
“…2,4 Although first-degree relatives of CVID subjects who have the same mutations are not commonly hypogammaglobulinemic, 5 activation of the mutant TACI on their B cells still fails to upregulate AICDA mRNA, revealing selective immune defects in these subjects. 6,7 Although TACI activation leads to B-cell activation, it also exerts selected inhibitory functions on B-cell expansion, best studied in mouse models. TACI 2/2 mice are deficient in antibody production to polysaccharide antigens but commonly develop severe lymphoproliferation, with increased numbers of B cells, enlarged spleens, and expanded peripheral B-cell populations leading to autoimmunity 1,8 and, in aging mice, lymphocytic infiltration of organs, membranoproliferative glomerulonephritis, and lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…BAFF-R expression is absent during the early stages of the B-cell lineage; its expression coincides with functional BCR expression by immature B cells in the bone marrow and is essential for Bcell survival and maturation [13,14,26,27]. TACI is mainly expressed on memory B cells and BCMA on plasmablasts and plasma cells [28][29][30]. A number of these molecules are therapeutic targets, as discussed later.…”
Section: B-cell Markers At Various Stages Of Maturationmentioning
confidence: 99%